Fano Resonances in Terahertz Metasurfaces: A Figure of Merit Optimization. Issue 11 (12th August 2015) - Cong, Longqing; Manjappa, Manukumara; Xu, Ningning; Al‐Naib, Ibraheem; Zhang, Weili; Singh, Ranjan
Abstract : An operation range of the figure of merit (FoM) that reflects the trade‐off between Q factor and resonance intensity of the Fano resonance is provided. The structural asymmetry parameter α = ( l 1 − l 2)/( l 1 + l 2) × 100% in the resonator determines the FoM that has an optimized band of operation for asymmetry ranging from 4% to 8% in the terahertz Fano resonant metasurfaces.